OBJECTIFICATION OF WOMEN IN MANDAR FOLKLORE: I PURA PARA'BUE, SAMBA' PARIA, MARA'DIA JAVA AND TO MINJARI DUYUNG - Asyrah,; Noer Jihad Saleh,; Herawaty Abbas, (International Journal of Social Science, 2022)
Folktale is part of classic literature that becomes the product of culture and disseminated as a reflection of a culture where the origin comes from. However, folktale characterization primarily for females character that is often described in powerless position because of poverty (weak economy), and careless until they take the wrong decision, thus they become the target of objectification. The researcher takes Mandarnese folktale as the object of this research to study the form of objectification that occurs to females character. This research is qualitative and descriptive. The researcher chose four folktales as the object of this research that was taken from the folktale book arranged by Bustan Basir Maras and colleagues entitled The Story of the Mandar People (Cari-Caritana To Mandar), The Stories of Mandarnese. The result of this research describes clearly the form of Nussbaum objectification version that found women as an object, objects of violation, women can be owned/bought/sold, and denial of subjectivity. In this research was also found that when women have power or supernatural ability they are often shown as sinister, and scary and need to be avoided because that is not a common phenomenon. But if it happened to men, they are often shown as powerful, dominant and strong.